Study on potential filter materials for use as substrate in constructed wetlands to strengthen phosphorus treatment performance from swine wastewater - Nguyễn, Thị Thương (2020)
Swine breeding industry is an important part of agriculture sector in Vietnam. In recent years, numerous large scales of pig farms have been developed to meet the pork demand in the market. According to General Statistics Office of Vietnam (2018), the whole country has about 500,000 livestock households, over 29 million pig heads, 3.8 million tons of meat. Also, as the pig producer, Vietnam is the biggest in ASEAN and the seventh biggest in the world. The swine breeding industry has promoted the economic development as well as the GDP of the country.